Study on the thermal cycle of Wire Arc Additive Manufactured (WAAM) carbon steel wall using numerical simulation - Mohsen Saadatmand; Reza Talemi (Fracture and Structural Integrity)
The thermal behavior in WAAM process is a significant cause for thermal stress. In this paper, a 3D model of a four-layer wall is built in ABAQUS software in order to investigate the thermal behavior in a carbon steel (ASTM A36) WAAM wall. Moreover, the effects of substrate preheating temperature and travel speed on the temperature distribution are studied. The modelling results show that with increase in number of deposited layers, the peak temperature increases but average cooling speed decreases. Furthermore, substrate preheating increases peak temperature of fist layer and decreases its average cooling speed. Regarding simulation results, the travel speed has major effects on the thermal behavior of deposited layers.